EUROPEAN PRIVATE LAW AND PUBLIC ORDER OF STATES (ABOUT THE MATTERS OF INAPPLICABILITY OF NORMS OF FOREIGN LAW) - A. V. Klemin (Russian Journal of Economics and Law)
Short description of European constitutional legislation is given in the article. Conception of «Public order» concerning sphere of international private law is considered.